(untitled) (Medical Forum Monthly, 2024)
Introduction: Subepidermal autoimmune blistering disorders (SEABD) are common in dermatological practice. Direct immunoflourescence (DIF) staining is considered gold standard for the diagnosis of these disorders. This study was conducted to determine the morphological and DIF patterns of these disorders. Study Design: Retrospective Study. Place and Duration of Study: This study was conducted at the department of Pathology, Basic Medical sciences Institute, Jinnah Postgraduate Medical centre, Karachi, from January 2002 to July 2007. Materials and Methods: Morphological and DIF patterns were recorded and categorical diagnoses of these disorders were established. Results: Bullous pemphigoid (BP) was found to the most frequent disorder with a relative frequency of 60.71% and mean age of 54.82 years. Relative frequencies of childhood bullous pemphigoid (Ch BP), dermatitis herpetiformis (DH), chronic bullous dermatosis of childhood (CBDC) and herpes gestationis (HG) were 10.71%, 14.28%, 10.71% and 3.57% respectively. Conclusion: Direct immunofluorescent staining is a one step procedure that should be done in all cases of SEABD. Use of salt split technique and immune electron microscopy would further enhance the level of certainty in SEABD. Key words: subepidermal blister, direct immunofluorescent staining, bullous pemphigoid